Initial Coefficients of Biunivalent Functions - See Keong Lee; V. Ravichandran; Shamani Supramaniam (Abstract and Applied Analysis)
An analytic function f defined on the open unit disk is biunivalent if the function f and its inverse f-1 are univalent in 𝔻. Estimates for the initial coefficients of biunivalent functions f are investigated when f and f-1, respectively, belong to some subclasses of univalent functions. Some earlier results are shown to be special cases of our results.